THE RELATIONSHIP BETWEEN LENS OPACITIES AND COLOR DISCRIMINATION ABILITY IN CATARACT PATIENTS - Solahuddin, Alie; Theodorus, Theodorus; Ariani, Dian (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Â Objective: To determine the relationship between lens opacities and color discrimination ability in cataract patients at the Special Eye Hospital in Palembang. Methods: A case study was undertaken in January to March 2017 at the Special Eye Hospital in Palembang. There were 80 cataract patients who met the inclusion and exclusion criteria. The relationship between lens opacities and color discrimination ability was analyzed using Spearman rho correlation test using SPSS version 18.0. Results: About 51.2% out of 80 cataract patients, most patients were diagnosed with nucleotide cataract with the majority degree of opacities is Grade III (50%). Average of total error score was 51.425Â±51, 441 (range 0-312). The correlation test results showed a significant weak positive correlation between lens opacities and color discrimination ability (r=0.376; p=0.001; n=80) where the percentage of effect of lens opacities to color discrimination ability was only 7.9% (R2=0.079). Conclusion: There was a significant weak positive correlation between lens opacities and color discrimination ability.